KINESICS AS A SET OF EXPRESSIVE MOVEMENTS iNCLUDED IN THE PROCESS OF COMMUNICATION - Jurayeva Shahnoza Sadullayevna (American Journals Publishing, 2024)
In this article non-verbal communication is one of the most important areas for the functioning of signs and symbolic information and occupies a significant place in the life of a person and society. In a narrow sense, Kinesics is a doctrine of gestures, primarily hand gestures. In addition, the object of kinesics are mimic gestures, gestures of the head and legs, postures, and symbolic movements.
Keywords: Kinesics, communication, Thumb up, confidence, Uzbek culture, shakes